2022
DOI: 10.1186/s40104-022-00772-6
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth retardation affects liver bile acid metabolism in growing pigs: effects associated with the changes of colonic bile acid derivatives

Abstract: Background Intrauterine growth retardation (IUGR) is associated with severely impaired nutrient metabolism and intestinal development of pigs. Our previous study found that IUGR altered intestinal microbiota and metabolites in the colon. However, the consequences of IUGR on bile acid metabolism in pigs remained unclear. The present study aimed to investigate the bile acid metabolism in the liver and the profile of bile acid derivatives in the colon of growing pigs with IUGR using bile acid targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Akkermansia improves intestinal barrier function 69 known to be altered in FGR models; 70 72 increases short-chain fatty acid production, 67 diminished in FGR pigs; 61 and facilitates bile acid metabolism, 62 altered in FGR piglets. 73 We also report positive correlation of lean mass with Akkermansia abundance in FGR males. Skeletal muscle mass is a major driver of insulin sensitivity 74 and known to be reduced across the lifespan in humans with FGR.…”
Section: Discussionsupporting
confidence: 61%
“…Akkermansia improves intestinal barrier function 69 known to be altered in FGR models; 70 72 increases short-chain fatty acid production, 67 diminished in FGR pigs; 61 and facilitates bile acid metabolism, 62 altered in FGR piglets. 73 We also report positive correlation of lean mass with Akkermansia abundance in FGR males. Skeletal muscle mass is a major driver of insulin sensitivity 74 and known to be reduced across the lifespan in humans with FGR.…”
Section: Discussionsupporting
confidence: 61%
“…Fusimonas intestini , a commensal species of the Lachnospiraceae family, highly colonizes obese and hyperglycemic humans and mice, producing long-chain fatty acids, such as elaidic acid, thus promoting diet-induced obesity ( Takeuchi et al., 2023 ). However, another study reported that the abundances of unclassified Mogibacteriaceae, Lachnospira , and Slackia exhibited significant negative correlations with dehydrolithocholic acid ( Liu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, key enzymes such as bile salt hydrolases, which can promote the conversion of conjugated bile acids to free bile acids, have been found in almost all bacterial phyla and archaeal systems [25]. In the intestines of growth-retarded piglets, the abundance of Bacteroidia was positively correlated with the contents of glycine-conjugated bile acids (such as GHCA), while the abundance of Lactobacillus was negatively correlated with GHCA and positively correlated with HCA levels [15]. Additionally, certain bacterial groups, such as Clostridium scindens, Clostridium hylemonae, Clostridium perfringens, and Peptostreptococcus hiranonis, have been found to regulate the epimerization of bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies have reported that hyodeoxycholic acid (HDCA) inhibits the proliferation and differentiation of IPEC-J2 cells and intestinal organoids [13,14]. Similarly, compared to normal piglets, the levels of LCA and dehydrocholic acid (DHCA) in the intestines of IUGR piglets were significantly increased, which may be the reason for the growth inhibition of IUGR piglets [15]. Due to the diverse range of BA types, the regulatory effects of different BAs on the intestine may be species-or tissue-specific or related to the physiological or pathological state of the body.…”
Section: Introductionmentioning
confidence: 95%